Analisis Penghinaan Terhadap Lembaga Peradilan (Contempt of Court) : Studi Kasus Pelanggaran Etik Pengacara Razman Arif Nasution - Akbar, Muhamad Dafi; Hayat, Gian Muzakir; Dimitri, Lucia Abrielle; Wildan, Ahmad; Siringoringo, Raymond Erlangga (Media Hukum Indonesia (MHI), 2025)
The phenomenon of contempt of court has garnered increasing attention in Indonesia’s legal practice, especially when such actions are committed by legal professionals such as advocates. This research is prompted by the case of Razman Arif Nasution, an advocate who allegedly committed contempt of court by making public statements that discredited judges and judicial proceedings. The purpose of this study is to analyze the form of contempt of court committed and examine the existing legal framework regulating and addressing such conduct in Indonesia. This research uses a normative juridical method with a case study approach. The findings indicate that Razman Arif Nasution’s actions violated the Indonesian Advocate Code of Ethics, particularly Article 6 point (c), and may also constitute criminal offenses under Articles 217 and 310 of the Indonesian Penal Code (KUHP). Although the new Criminal Code (Law No. 1 of 2023) begins to regulate contempt of court in a more structured manner, there remains a need for a dedicated and comprehensive law. This study underscores the importance of establishing specific legislation and strengthening the enforcement of professional ethics for advocates.